THE EFFECTIVENESS OF USING KAHOOT! TO TEACH NARRATIVE TEXT: A REFLECTIVE ANALYSIS IN INDONESIA - Dina Rafidiyah; Hafizhatu Nadia; Ceria Hermina; Azaria Nur Azizah; Muhammad Julian Adhitama (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2022)
Being taught reading is vital to fulfilling students' needs for academic success. To reach that requirement, teachers should teach reading comprehension in an entertaining way through technology. Kahoot! is one of the online applications used for teaching English with positive responses from students. This research project was done in one public high school in Banjarmasin, Indonesia. One hundred five students divided into six classes participated as study subjects. The research used a mixed-method approach, first analyzing quantitative data from a survey and qualitative data to give better insight into teacher and students' perceptions of their narratives. A framework for a lesson has been presented in this study, where it can be modified and implemented in lessons. The said framework used Kahoot! in teaching narrative text and was favored by the teacher. Both from the reflection of the teacher and students, Kahoot! gave students an enjoyable way to learn the narrative text, as well as giving more chances for them to decrease their anxiety and increase their motivation to learn English. Although the teacher found many obstacles to implementing Kahoot! in his teaching practice, at the end of the day, he considered his students active and excited to learn narrative text and plans to use Kahoot! for his future classes. The implication of this study was to encourage teachers to reflect on their students' feelings and level of engagement. Future studies can focus on the use of Kahoot! for another type of text or even for other skills.